2016
DOI: 10.1016/j.biomaterials.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter intra-arterial infusion of doxorubicin loaded porous magnetic nano-clusters with iodinated oil for the treatment of liver cancer

Abstract: A promising strategy for liver cancer treatment is to deliver chemotherapeutic agents with multifunctional carriers into the tumor tissue via intra-arterial (IA) transcatheter infusion. These carriers should release drugs within the target tissue for prolonged periods and permit intra-procedural multi-modal imaging of selective tumor delivery. This targeted transcatheter delivery approach is enabled via the arterial blood supply to liver tumors and utilized in current clinical practice which is called chemoemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…These findings reinforce the selective nature of antibody-coated HNPs to reach receptorpositive cells, as shown in a recent study (38). Furthermore, cytotoxicity of anti-MG1 HNPs was analogous to the cell viability data of different iron oxide nanoparticles in our previous study (33) or polymer-coated iron oxide nanoparticles (39) and hybrid gold-iron oxide nanoparticles reported in other studies (40). These results also support prior observations on changes in particle size, and the gold shell had minimal effect on the cytotoxicity profiles of HNPs (40).…”
Section: Mr Imagingsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings reinforce the selective nature of antibody-coated HNPs to reach receptorpositive cells, as shown in a recent study (38). Furthermore, cytotoxicity of anti-MG1 HNPs was analogous to the cell viability data of different iron oxide nanoparticles in our previous study (33) or polymer-coated iron oxide nanoparticles (39) and hybrid gold-iron oxide nanoparticles reported in other studies (40). These results also support prior observations on changes in particle size, and the gold shell had minimal effect on the cytotoxicity profiles of HNPs (40).…”
Section: Mr Imagingsupporting
confidence: 91%
“…Therefore, we focused our efforts on bolstering the tumor-specific delivery of nanoparticles and on performing targeted PTA while concurrently exploring different imaging modalities. We and other groups have shown that iron oxide-based nanomaterial is suitable to monitoring targeted delivery of therapeutics in preclinical liver tumor models (33,34). Methods to engineer magnetic nanoparticles for the development of new drug and delivery platforms are under intense investigation (35).…”
Section: Mr Imagingmentioning
confidence: 99%
“…AB NPs also showed higher photo cytotoxicity (IC 50 ≈6.0 µg mL −1 , equivalent to aza‐BODIPY concentration) than its dark toxicity (with 70% cell viability at the concentration of 8 µg mL −1 , equivalent to aza‐BODIPY concentration). The cytotoxicity of free DOX was the highest among these materials (with IC 50 ≈1.8 µg mL −1 , equivalent to DOX concentration), which could be ascribed to DOX's easy diffusion through cellular membrane, thereby resulting in opening the antitumor function of free DOX . All the results indicate that both DAB NPs and AB NPs possess high photo cytotoxicity, low dark cytotoxicity and good biocompatibility in HeLa cells.…”
Section: Resultsmentioning
confidence: 89%
“…These results suggest that the sustained release of Dox pMNCs can be significantly potentiated by lipiodol for increased retention. Finally, MRI and histological evaluations revealed that the long-term drug release and retention of Dox-pMNCs within iodinated oil significantly enhanced liver cancer cell death [31].…”
Section: Doxorubicin Loaded Porous Magnetic Nano Clusters With Lipiodolmentioning
confidence: 98%